Effectiveness of Stalevo Drug Usage in Parkinson's Patients: A Narrative Review - M Andri Prasetyo; Fauna Herawati (Jurnal Penelitian Pendidikan IPA, 2026)
Parkinson's Disease (PD) is a neurodegenerative disorder that affects patients' quality of life, with primary motor symptoms such as tremor, muscle rigidity, and bradykinesia. Levodopa is the mainstay of PD therapy, but approximately 80% of patients experience motor complications, such as motor fluctuations and "wearing-off" after several years of therapy. This study evaluates the efficacy, safety, and rational use of Stalevo (levodopa, carbidopa, and entacapone) in managing motor complications and "wearing-off" phenomena in patients with Parkinson's Disease (PD). This research was conducted as a narrative review to provide a recent evidence-based synthesis of the efficacy and safety of Stalevo. Methods included a search of articles in PubMed, ScienceDirect, and Google Scholar published between 2015 and 2025 using the keywords "Stalevo" and "Parkinson's disease." The study revealed that Stalevo was effective in prolonging the duration of levodopa's effect, reducing the required levodopa dose, and improving patients' quality of life, particularly in patients with motor fluctuations. Although side effects such as dyskinesia and diarrhea may occur, Stalevo's overall safety profile is well-received. Stalevo is a cost-effective, evidence-based intervention for intermediate-to-advanced PD. Rational use requires precise patient selection and monitoring for dopaminergic side effects, such as dyskinesia and diarrhea, to optimize quality of life and ensure patient safety.